Awakening and Contribution of Muslim Intellectuals to Establish Islamic Civilization - Fahmi Amhar (Islamic Research, 2022)
Islamic civilization is a civilization built on the basis of the Islamic creed (aqeeda), by the Islamic community and for the purposes dictated by Islam. Islamic civilization must be rebuilt for two big reasons: the world's civilization major threats, and help the Islamic mastery so many fardhu kifayah of Muslims that do not run normally. Intellectual Muslims are Muslims who have an education above the population average, and care about the problems of the Ummah. Intellectual Muslims are obliged to contribute, because they are people who were given by Allah the trust of reason and the trust of knowledge, so they have a greater responsibility. Throughout history, these Muslim intellectuals have made many contributions: as inspirator, guardian of the scientific method, and guardians of applying science and technology responsibly. Some think that this ummah is slumped because it is weak in modern science and technology. But the reality is far more complicated. This is when Muslim intellectuals realize that they are part of the best of the ummah, who must bring to this world the best works, who have the responsibility to remind people, enjoin what is right, and prevent what is evil prove faith in Allah. This is the time for them to sit down together to integrate and synergize all their potential and solve the people's problems.